The Level of Obesity and the Incidence Varicose Vein on Adult Patients in Public Health Center Mijen - Tri Sakti Widyaningsih; Yulianus Prabu; Menik Kustriyani (Alliance oh Health Activists (AloHA), 2018)
Background: Preliminary studies conducted by researchers on December 2015 at Public Health Center Mijen, Semarang get a yield of 7 people in the category of obesity, be found 2 people have a varicose veins in the legs and 5 other people not have varicose veins in the legs. Aim: Analyzing correlation between the level of obesity with events varicose vein on adult patients aged 26-45 years old in Public Health Center Mijen, Semarang. Methods: The research design was cross sectional. Samples were taken from adult obese patients who come to the Public Health Center Mijen Semarang as much as 42 respondents, selected by accidental sampling technique. Data were gathered using observation sheets, then analyzed using Spearman rank test. Results: The p-value of the Spearman rank test was 0.003, with the correlation coefficient of 0.443. Conclusion: There is a correlation between the level of obesity with the incidence of varicose veins on adult patients in Public Health Center Mijen Semarang. Suggestion: Recommended for respondent to control weight and attention intake foods consumed. Keywords: Obesity; varicose vein, adult